2018
DOI: 10.1111/jam.14095
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae-bacteria symbiosis in microalgal growth and biofuel production: a review

Abstract: Photosynthetic microalgae can capture solar energy and convert it to bioenergy and biochemical products. In nature or industrial processes, microalgae live together with bacterial communities and may maintain symbiotic relationships. In general interactions, microalgae exude dissolved organic carbon that becomes available to bacteria. In return, the bacteria remineralize sulphur, nitrogen and phosphorous to support the further growth of microalgae. In specific interactions, heterotrophic bacteria supply B vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(93 citation statements)
references
References 72 publications
0
92
0
1
Order By: Relevance
“…In the future, diatoms will remain as the best candidate for biofuel production. Some strain of diatoms produces lipids as 50% to 80% of the dry weight that can be used in the production of biofuel thereby focusing on the role of diatoms as an ideal substitute for fossil fuels [ 16 ]. Despite having all these important characteristics, they are the least explored aquatic species because isolation and maintenance of axenic culture is a tedious job [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the future, diatoms will remain as the best candidate for biofuel production. Some strain of diatoms produces lipids as 50% to 80% of the dry weight that can be used in the production of biofuel thereby focusing on the role of diatoms as an ideal substitute for fossil fuels [ 16 ]. Despite having all these important characteristics, they are the least explored aquatic species because isolation and maintenance of axenic culture is a tedious job [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was possible that the endosymbiotic green algae Chlorella sp. became more carbon-rich at higher temperatures (Serra-Maia et al, 2016), which could supply more organic matter to the symbiotic Pseudomonas species (Yao et al, 2019). An opposite trend was observed for the dominant DRB group in the algae-free ciliate E. vannus, in which the relative abundance of Pseudoalteromonas species decreased progressively with the increase of temperature ( Figure 4A).…”
Section: Warming Selected Specific Bacterial Species In Association Wmentioning
confidence: 99%
“…Many studies have shown that cyanobacteria live in symbiosis with heterotrophic bacteria. These supply the cyanobacteria with important secondary metabolites and in return receive carbohydrates or nitrogen compounds (Thompson et al 2012;Kouzuma and Watanabe 2015;Yao et al 2019).…”
Section: Heterotrophic Cultivationsmentioning
confidence: 99%